2011
DOI: 10.1155/2011/678570
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell Death byM. tuberculosisas a Strategy for Pathogen Survival

Abstract: It has been clearly demonstrated that in vitro, virulent M. tuberculosis can favor necrosis over apoptosis in infected macrophages, and this has been suggested as a mechanism for evading the host immune response. We recently reported that an effect consistent with this hypothesis could be observed in cells from the blood of TB patients, and in this paper, we review what is known about evasion strategies employed by M. tuberculosis and in particular consider the possible interaction of the apoptosis-inhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 132 publications
0
30
0
Order By: Relevance
“…The literature on the inhibition of host cell apoptosis by Mtb has been reviewed recently (Abebe et al 2011;Behar et al 2011;Briken 2013). The mechanisms of inhibition include the up-regulation of host cell antiapoptosis signaling proteins such as the Bcl-2 family member Mcl-1 (Sly et al 2003) or the Bfl-1 protein (Kausalya et al 2001).…”
Section: Manipulation Of Apoptosis Pathways By Mtbmentioning
confidence: 99%
“…The literature on the inhibition of host cell apoptosis by Mtb has been reviewed recently (Abebe et al 2011;Behar et al 2011;Briken 2013). The mechanisms of inhibition include the up-regulation of host cell antiapoptosis signaling proteins such as the Bcl-2 family member Mcl-1 (Sly et al 2003) or the Bfl-1 protein (Kausalya et al 2001).…”
Section: Manipulation Of Apoptosis Pathways By Mtbmentioning
confidence: 99%
“…The IFN-γ/IL-4 ratio was increased in most patients during therapy but was decreased in contacts that become ill, suggesting that this state is a direct consequence of the disease [30]. The IFN-γ/IL-10 ratio increased in mice with α-mangostin therapy and it means that the administration α-mangostin associated with a cure of pulmonary TB.…”
Section: Discussionmentioning
confidence: 97%
“…Apoptosis leads not only to disposal of digested apoptotic cells with mycobacteria and their elimination in phagosomes, but also to an efficient processing of mycobacterial antigens used by antigen-presenting cells for the maintenance and enhancement of the immune response to the pathogen [24]. It has been established that in vitro infection of different cell types with non-virulent strains of mycobacteria led these cells to rapid death by TNFα-induced receptor-dependent apoptosis [48,52,65]. However, our previous studies using the ex vivo model of granulomatous inflammatory lesions in mice did not reveal, at any time of latent tuberculous infection, morphological signs of apoptotic or necrotic death in granuloma macrophages or dendritic cells differently loaded with mycobacteria of the attenuated BCG strain [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that mycobaterial strains have different effects on cell death induction in vitro [24]. Nonvirulent Mycobacterium tuberculosis strain H37Ra and attenuated Mycobacterium bovis bacillus Calmette-Guérin (BCG) caused apoptosis of infected macrophages and the elimination of bacteria, while virulent mycobacterial strains (M. tuberculosis H37Rv, Erdman and M. bovis) actively reproduced in the cells and acted to prevent their death in vitro [45][46][47][48]. It has also been found that only virulent M. tuberculosis H37Rv induced expression of the Mcl-1 protein, an antiapoptotic member of the Bcl-2 family, after in vitro infection of human THP-1 cells [49].…”
Section: Introductionmentioning
confidence: 99%